2021
DOI: 10.1101/2021.10.12.464102
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modulation of pre-mRNA structure by hnRNP proteins regulates alternative splicing of MALT1

Abstract: Alternative splicing is controlled by differential binding of trans-acting RNA binding proteins (RBPs) to cis-regulatory elements in intronic and exonic pre-mRNA regions. How secondary structure in the pre-mRNA transcripts affects recognition by RBPs and determines alternative exon usage is poorly understood. The MALT1 paracaspase is a key component of signaling pathways that mediate innate and adaptive immune responses. Alternative splicing of MALT1 exon7 is critical for controlling optimal T cell activation.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Further exploration was conducted on the circANKRD42 regulatory mechanism of hucMSCs treatment. Heterogeneous nuclear ribonucleoprotein L (hnRNP L) is an alternative RNA splicing factor involved in RNA splicing biogenesis [21]. Immunofluorescence images depicted that hnRNP L was located in the nucleus with or without hucMSCs/TGF-β1 treatment.…”
Section: Hucmscs Treatment Alleviated Pulmonary Fibrosis By Regulatin...mentioning
confidence: 99%
“…Further exploration was conducted on the circANKRD42 regulatory mechanism of hucMSCs treatment. Heterogeneous nuclear ribonucleoprotein L (hnRNP L) is an alternative RNA splicing factor involved in RNA splicing biogenesis [21]. Immunofluorescence images depicted that hnRNP L was located in the nucleus with or without hucMSCs/TGF-β1 treatment.…”
Section: Hucmscs Treatment Alleviated Pulmonary Fibrosis By Regulatin...mentioning
confidence: 99%
“…Recent studies have also shown the involvement of HNRNPU in mitosis and cell division by changing its interactions with condensed chromatin and influencing DNA replication and sister chromatid separation (Connolly et al, 2022; Ma et al, 2011; Sharp et al, 2020). Several studies have reported a role for HNRNPU in splicing, promoting both exon inclusion and exclusion (Huelga et al, 2012; Jones et al, 2022; Ye et al, 2015). Mechanistically, it has been shown that HNRNPU can stabilize the pre-mRNA structure, thus inhibiting the splicing of certain exons (Jones et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported a role for HNRNPU in splicing, promoting both exon inclusion and exclusion (Huelga et al, 2012; Jones et al, 2022; Ye et al, 2015). Mechanistically, it has been shown that HNRNPU can stabilize the pre-mRNA structure, thus inhibiting the splicing of certain exons (Jones et al, 2022). A critical role for Hnrnpu mediated splicing has also been demonstrated during pre- and postnatal heart development in mice, showing that loss of Hnrnpu leads to increased intron retention events, causing abnormality in heart development and function (Ye et al, 2015).…”
Section: Introductionmentioning
confidence: 99%